Simulation of Wind Speed in the Ventilation Tunnel for Surge Tanks in Transient Processes - Jiandong Yang; Huang Wang; Wencheng Guo; Weijia Yang; Wei Zeng (Energies, 2016)
Hydroelectric power plants’ open-type surge tanks may be built in mountains subject to the provision of atmospheric air. Hence, a ventilation tunnel is indispensable. The air flow in the ventilation tunnel is associated with the fluctuation of water-level in the surge tank. There is a great relationship between the wind speed and the safe use and project investment of ventilation tunnels. To obtain the wind speed in a ventilation tunnel for a surge tank during transient processes, this article adopts the one-dimensional numerical simulation method and establishes a mathematical model of a wind speed by assuming the boundary conditions of air discharge for a surge tank. Thereafter, the simulation of wind speed in a ventilation tunnel, for the case of a surge tank during transient processes, is successfully realized. Finally, the effective mechanism of water-level fluctuation in a surge tank and the shape of the ventilation tunnel (including length, sectional area and dip angle) for the wind speed distribution and the change process are discovered. On the basis of comparison between the simulation results of 1D and 3D computational fluid dynamics (CFD), the results indicate that the one-dimensional simulation method as proposed in this article can be used to accurately simulate the wind speed in the ventilation tunnel of a surge tank during transient processes. The wind speed fluctuations can be superimposed by using the low frequency mass wave (i.e., fundamental wave) and the high frequency elastic wave (i.e., harmonic wave). The water-level fluctuation in a surge tank and the sectional area of the ventilation tunnel mainly affect the amplitude of fundamental and harmonic waves. The period of a fundamental wave can be determined from the water-level fluctuations. The length of the ventilation tunnel has an effect on the period and amplitude of harmonic waves, whereas the dip angle influences the amplitude of harmonic waves.